Types of entrepreneurs in the conversion process of economic functions in towns: Paraty case study (Rio de Janeiro state) - Bayma,Fátima (2013)
The aim of this paper is to discuss the results of a study designed to identify different types of entrepreneurs in the process of converting economic functions of the town of Paraty, Rio de Janeiro State, and to analyze the characteristics of these entrepreneurs and their modi operandi in this process. The theoretical review included research about the processes for the conversion of urban economic functions and types of entrepreneurship. We conducted a qualitative study based on the case study method, using 23 interviews and documentary analysis. As a result, we found that there were traditional, modern and postmodern entrepreneurs in Paraty, mobilizing capital and creating alliances and disputes within the dynamics of the town’s economic function conversion process.